A METHOD OF ENSURING DATA INTEGRITY IN THE FIELD OF REAL ESTATE REGISTRATION USING SMART CONTRACTS - FEDORENKO, VLADYSLAV; PASICHNYK, OLEKSANDR; SKRYPNYK, TETIANA; MANZIUK, EDUARD (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Ensuring data integrity is quite relevant in an increasingly important world, and this is no coincidence. Registration of real estate is a key element of the functioning of society, as it affects legal relations, the financial condition of citizens, and has a significant impact on the country`s economy as a whole. Blockchain technology is based on the creation of two lists of data, where individual elements, known as blocks, are linked together in a chain using cryptography. One of the key features of the blockchain is its open and decentralized data storage. This means that any user can check the transaction history or data stored on the blockchain without having to rely on an intermediary. This transparent access to information make blockchain particularly useful for financial transactions, where reliability and trust are important. For many people, blockchain is primarily associated with cryptocurrencies such as Bitcoin. It is used to secure financial transactions and store transaction history. However, this technology is not only used in the financial sector. Blockchain can be used to process virtually any data of great value, including medical records, supply chain management systems, vote transformation during elections, and many other applications. Blockchain is an innovative technology that is actively used in various, industries, such as economics, finance, medicine, legal and others. However, the use of blockchain and smart contracts in the real estate sector is still insufficiently researched. This study examines the advantages and disadvantages of using blockchain and smart contracts, and propose a secure system for concluding real estate transactions using these technologies. Blockchain provides, the ability to create secure and reliable records of property ownership, transaction, and history. Each data block in the blockchain contains information about a specific property and all transactions related to it. This information is confirmed by the user network and remains unchanged, which guarantees the historical accuracy and reliability of the data.